Educational Initiatives and Governance Practices of the Local Government Unit of Hingyon - Seridon, Sherdie; Bastian, Rosemelita (Azal Arts and Humanities, 2026)
This study examined the educational initiatives and governance practices of the Local Government Unit (LGU) of Hingyon and determined how these contributed to the improvement of local education services. Using a quantitative descriptive–correlational research design, the study involved school administrators, teachers, and selected community stakeholders who were directly involved in or beneficiaries of LGU-led educational programs. Data were gathered through a validated survey questionnaire assessing educational initiatives in terms of access, quality of programs, learner and teacher support, and community involvement, as well as governance practices in terms of leadership, transparency, accountability, participatory decision-making, and policy implementation. Descriptive statistics and Pearson’s product–moment correlation coefficient were used to analyze the data. Findings revealed that the educational initiatives of the LGU of Hingyon were rated very high, particularly in improving access to education and strengthening community involvement. Governance practices were also rated very high, with leadership and accountability emerging as the strongest dimensions. The perceived effectiveness of educational initiatives was similarly rated very high, especially in enhancing school resources, learner welfare, and school- community partnerships, although program sustainability received relatively lower ratings. Correlation analysis indicated a significant positive relationship between governance practices and the effectiveness of educational initiatives, suggesting that stronger governance practices were associated with more effective education programs. The study concludes that sound governance practices play a critical role in ensuring the success of LGU-led educational initiatives, particularly in rural and mountainous contexts such as Hingyon. Strengthening participatory decision-making, monitoring mechanisms, and long-term planning is recommended to sustain and further enhance the impact of local education initiatives. The findings provide context-specific evidence that can inform policymakers, educators, and local leaders in improving educational governance and service delivery.